Learning achievement reviewed from self regulated learning, future orientation, and parental support - Yuzarion, Yuzarion; Agustiana, Aulia Kartika; Alfaiz, Alfaiz; Yandri, Hengki; Musdizal, Musdizal; Aulia, Rahmadianti (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This study aimed to answer the main problem whether learning achievement could be viewed from self-regulated learning, future orientation and parental support to obtain empirical support. This research used quantitative methods, the sample of 103 people. The data was collected with instruments, scale (1) self-regulated learning, (2) future orientation and (3) parental support. Learning achievement used report card grades. The results showed that learning achievement could be viewed from self-regulated learning, future orientation and parental support. It got very significant empirical support., score F reg=43,155 dan p=0,000 (p<0,01). Self-regulated learning, future orientation, and parental support provided an effective contribution of 55.4% to learning achievement. The biggest SE was from parental support 37.4%, followed by self-regulated learning 12.7%, and future orientation 6.6%. Based on the findings, the researcher suggests: (1) parents need to maximize learning support for children, strengthen emotional support, instrumental, and informative support. (2) teachers need to introduce self-regulated learning to students. (3) teachers and parents to explore the future orientation of children or students well, so that they grow stronger for a more planned future. And (4) researchers recommend the following research in elementary, junior high, senior high school and PT.